Accuracy of a new instrument for noninvasive evaluation of pulse wave velocity: the Arterial sTiffness faitHful tOol aSsessment project. Issue 11 (13th November 2021) - Leone, Dario; Buraioli, Irene; Mingrone, Giulia; Lena, Davide; Sanginario, Alessandro; Vallelonga, Fabrizio; Tosello, Francesco; Avenatti, Eleonora; Cesareo, Marco; Astarita, Anna; Airale, Lorenzo; Sabia, Luca; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Large artery stiffness, assessed by carotid–femoral pulse wave velocity (cfPWV), is a major risk factor for cardiovascular events, commonly used for risk stratification. Currently, the reference device for noninvasive cfPWV is SphygmoCor but its cost and technically challenging use limit its diffusion in clinical practice. Aim: To validate a new device for noninvasive assessment of cfPWV, ATHOS (Arterial sTiffness faitHful tOol aSsessment), designed in collaboration with the Politecnico di Torino, against the reference noninvasive method represented by SphygmoCor. Methods: Ninety healthy volunteers were recruited. In each volunteer, we assessed cfPWV, using SphygmoCor (PWVSphygmoCor ) and ATHOS (PWVATHOS ) devices in an alternate fashion, following the ARTERY Society guidelines. The accuracy was assessed by Bland–Altman plot, and reproducibility was assessed by interoperator correlation coefficient (ICC). Results: Mean PWVATHOS and mean PWVSphygmoCor were 7.88 ± 1.96 and 7.72 ± 1.95 m/s, respectively. Mean difference between devices was 0.15 ± 0.56 m/s, with a high correlation between measurements ( r = 0.959, P < 0.001). Considering only PWV values at least 8 m/s ( n = 30), mean difference was 0.1 ± 0.63 m/s. The ICC was 97.7% with ATHOS Conclusion: ATHOS showed an excellent level of agreement with SphygmoCor, even at high PWV values, with a good reproducibility. Its simplicity of use could help increase clinical application of PWV assessment, improving patients' cardiovascular risk stratification.